Seng Batik: Traditional Colours, Innovation, and Empowerment of the Sengguruh Village Community - Anisya Ramadhanty; Hanum Tri Utami; Intan Kurnia Wijaya; Kaira Noviza; Vivi Apriliyani; Guteres, Dian Karisma Septiana; Farida Ratna Dewi (Prospect Publishing, 2025)
The preservation of batik as Indonesia's cultural heritage faces challenges in the era of modernization, where the interest of the younger generation is declining and the economic opportunities for local communities are still limited. In fact, batik has aesthetic and philosophical values, as well as cultural identity that is important to preserve. This study aims to describe the role of Batik Seng, a batik brand from Sengguruh Village, Kepanjen Subdistrict Malang Regency, in integrating tradition, innovation, and community empowerment. The research method used a qualitative approach through semi-structured interviews with the founders and craftsmen of Batik Seng, as well as observations at the production site. The analysis was conducted using descriptive-qualitative methods with the stages of reduction, presentation, and conclusion drawing. The results show that Batik Seng presents innovations in the form of hand-drawn batik, stamped batik, jumputan, and ecoprint using natural dyes and recycled wax waste so that it can be reused. Community empowerment focuses on vulnerable groups, such as people with disabilities, the elderly, school dropouts, and productive housewives. Support from PLN Nusantara Power UP Brantas District A (Sutami Hydroelectric Power Plant) through the Wastewater Treatment Plant (IPAL) facility and mentoring strengthens the sustainability of production. In addition, Ms. Evi's role as a local hero is important in knowledge transfer, including to the younger generation. Digital marketing strategies and participation in exhibitions have helped expand market reach. This study confirms that Batik Seng can serve as an inspirational model for the development of a culture-based creative economy through a combination of tradition, innovation, and environmental awareness.